Ring finger protein 5 mediates STING degradation through ubiquitinating K135 and K155 in a teleost fish - Qin, Xiaowei; Li, Chuanrui; Liang, Mincong; Qian, Zhen; You, Yanlin; Weng, Shaoping; He, Jianguo; Guo, Changjun (Frontiers in Immunology, 2024)
Stimulator of interferon genes (STING) is a key connector protein in interferon (IFN) signaling, crucial for IFN induction during the activation of antiviral innate immunity. In mammals, ring finger protein 5 (RNF5) functions as an E3 ubiquitin ligase, mediating STING regulation through K150 ubiquitylation to prevent excessive IFN production. However, the mechanisms underlying RNF5’s regulation of STING in teleost fish remain unknown. This study investigated the regulatory role of the mandarin fish (Siniperca chuatsi) RNF5 (scRNF5) in the STING-mediated antiviral immune response and identified the specific regulatory sites on scSTING. Furthermore, an examination of scRNF5 expression patterns in virus-infected cells revealed its responsiveness to mandarin fish ranavirus (MRV) infection. The ectopic expression of scRNF5 suppressed scSTING-mediated IFN signaling and facilitated MRV replication. Co-immunoprecipitation experiments indicated an interaction between scRNF5 and scSTING. The further experiments demonstrated that scRNF5 exerted its inhibitory effect by promoting the degradation of scSTING, which was observed to be blocked by MG132 treatment. Ubiquitination assays with various scSTING mutants showed that scRNF5 catalyzed the ubiquitination of scSTING at K135 and K155 residues. Furthermore, we provided evidence that scRNF5 significantly attenuated scSTING-dependent antiviral immunity by targeting negative regulators within the scSTING signaling cascade. This study underscored that RNF5 negatively regulated the STING-mediated IFN signaling pathway in mandarin fish, attenuated STING’s antiviral activity, and facilitated STING degradation via the ubiquitin-proteasome pathway at two novel lysine sites (K135 and K155). Our work offered valuable insights into the regulatory mechanisms of STING-mediated signaling in teleost fish, paving the way for further research.